miRNA-based signature for predicting epithelial ovarian cancer recurrence - De Cecco, Loris; Bagnoli, Marina; Canevari, Silvana; Califano, Daniela; Perrone, Francesco; Pignata, Sandro; Mezzanzanica, Delia (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
We thank Ceppi and coauthors (1) for their comments on our recent paper on the identification of a miRNA-based signature predicting early relapse/progression in ovarian cancer patients (2). Epithelial ovarian cancer (EOC) is still the commonest cause of gynecological cancer-related death mainly due to the difficult early diagnosis and to the high frequency of patients eventually developing an incurable state of platinum-resistant disease (3). The selection of patients at higher risk of relapse is therefore an urgent need to improve the design of tailored therapies.